The effects of supine and prone positions on oxygenation in premature infants undergoing mechanical ventilation - Abdeyazdan, Zahra (Medknow Publications Pvt Ltd, 2010)
BACKGROUND: Since the use of high concentrations of oxygen in infants may lead to chronic lung problems, using proper methods of care in infants under mechanical ventilation is one of the most important measures in NICU. This study aimed to investigate the effects of prone and supine positions on oxygenation (SPO(2)) in premature infants under mechanical ventilation and comparing infants’ oxygenation in the two positions. METHODS: In across over non randomized clinical trial study, 32 preterm infants under mechanical ventilation who had inclusion criteria were enrolled in simple convenient method. Firstly, they were placed in supine position for 120 minutes and further in prone position for 120 minutes .Their SPO(2) were monitored by pulse oximeter continuously and was recorded every minute. Data analysis was done using Software SPSS(15) by ANOVA test and post hoc test. RESULTS: The data showed that during 120 minutes of exposure of infants in each position there were no significant changes in SPO(2). In addition, the SPO(2) levels in the prone position were significantly higher than the SPO(2) levels in the supine position from 15(th) minute to 120(th) minute (to the end). CONCLUSIONS: Neonatal positioning in prone position is a simple, non-invasive, and free of charge method that could lead to improve oxygenation in infants undergoing mechanical ventilation.